PENGARUH INNOVATION CAPABILITY DAN BLUE OCEAN STRATEGY TERHADAP COMPETITIVE ADVANTAGE DAN BUSINESS PERFORMANCE - Zainurrafiqi Zainurrafiqi; Siti Salama Amar (Assyarikah: Journal of Islamic Economic Business, 2021)
Batik SMEs in Pamekasan Regency need the right strategy in realizing Competitive Advantage and Business Performance, Innovation Capability and Blue Ocean Strategy are two things that can be considered by Pamekasan Regency Batik SMEs to realize Competitive Advantage and Business Performance. The present research was Eksplanatory research. The purpose of this research is to analyze the role of Innovation Capability and Blue Ocean Strategy as antecedents of Competitive Advantage. The data is distributed to 300 managers of Batik SMEs in Pamekasan Regency. Data analysis was carried out using the Structural Equation Model (SEM). The results of data analysis show that Innovation Capability has a positive and significant effect on Competitive Advantage, Blue Ocean Strategy has a positive and significant effect on Competitive Advantage and Competitive Advantage has a positive and significant impact on Business Performance.